Prinsip-Prinsip Pembelajaran Bahasa - Fitri Kholilah Nasution; Sa’idatul Hasanah; Siti Munawwaroh; Syakira Anandia (Universitas Dehasen Bengkulu, 2022)
Indonesian language learning activities definitely require principles in it. In order for learning to run according to the desired goals, therefore this article aims to discuss several principles in the learning system. This research method uses library research methods quoted from several journals and books. The results of the study can be concluded that in learning must have principles, because with the principle of being able to instill a form of effort in realizing learning objectives.